KAZAKHSTAN’S RUSSIAN DIASPORA: BETWEEN MIGRATION AND SEARCH OF A NEW IDENTITY - Assanbayev Mukhit B.; Hanks Reuel R. (Scientific Journal of Pedagogy and Economics, 2020)
The article proposes the Hirschman’s model of studying the changes in the Russian Diaspora’s perception of Kazakhstan as their new host-state. After the demise of the Soviet Union, their responses to decline of their political, social and cultural status varied from voicing discontent to exiting and loyalty throughout the nonRussian former Soviet republics, where they found themselves living in a new political reality. Not surprisingly their observable public sentiment went through a variety of negative expressions, such as confusion, desperation and even feelings of betrayal resulting from the need to learn new national languages and adapt to emerging nationalizing policies and practices of their new host-states. Many Russian people perceived the unexpected collapse of their common Soviet homeland as a personal drama, and some of these continue to identify more as countrymen of Russia rather than their homeland. This has become and will remain the main source of emigration aspirations among Russian Diasporas living in the former Soviet republics. The article draws upon the case of the Russian Diaspora living in Kazakhstan, where, even after three decades of national independence, many Russians still remain confused and too aloof to actively participate in the political and social life of the country.